Impact of Distracting Emotional Stimuli on the Characteristics of Movement Performance: A Kinematic Study - Lu, Yingzhi; Wang, Tianyi; Long, Qiuping; Cheng, Zijian (Frontiers in Psychology, 2021)
It is well documented that emotional stimuli impact both the cognitive and motor aspects of ‘goal-directed’ behavior. However, how emotional distractors impact motor performance remains unclear. This study aimed to characterize how movement quality was impacted during emotional distractors. We used a modified oddball paradigm and documented the performance of pure movement. Participants were designated to draw a triangle or a polygon, while an emotional stimulus was presented. Speed was assessed using reaction time and movement time. The quality and precision of movement were assessed by calculating the accuracy and root-mean-square error (RMSE). Compared to drawings of triangles, polygons had higher accuracy under negative stimuli, but lower RMSE under positive stimuli. The results indicate that distracting emotional stimuli impact different aspects of movement quality, with movement complexity influencing accuracy under negative distractors and precision under positive distractors. This study provides further evidence that movement precision is an important feature of emotional embodiment that should be incorporated in future studies.